EFL TEACHERS' SCAFFOLDING BEHAVIOR IN TEACHING ENGLISH USING COOPERATIVE LEARNING AT SMP NEGERI 40 MAKASSAR - Raisah Adiela; La Sunra; Amra Ariyani3 Ariyani (State University of Makassar, 2026)
This study aims to describe the scaffolding behavior of EFL teachers in teaching English through cooperative learning at SMP Negeri 40 Makassar, and to identify the challenges they face. A descriptive qualitative design was employed. Two English teachers, referred to as Teacher A and Teacher S, were selected through purposive sampling on the criteria of at least two years' teaching experience and the regular use of cooperative learning. Data were collected through four non-participant classroom observations of eighty minutes each, using a checklist based on Wood, Bruner, and Ross's (1976) six scaffolding functions, and through semi-structured interviews with each teacher. The data were analyzed using Miles, Huberman, and Saldaña's (2014) interactive model. The findings show that both teachers performed all six scaffolding functions, which operated as an integrated whole rather than as separate techniques. The two teachers realized the same functions through different means: Teacher A worked through staged worksheets, guiding questions, and task segmentation, while Teacher S worked through direct facilitation, physical demonstration, and a gradual release of responsibility. Emotional support emerged as a substantial part of both teachers' practice, indicating that in EFL classrooms affective support works alongside cognitive support. Cooperative learning did not produce collaboration automatically; the teachers scaffolded students into it before, during, and after group work. The main challenges reported were limited time, judging when to withdraw support, accommodating different levels of ability, and engaging passive students.Keywords: scaffolding behavior; cooperative learning; EFL teaching; teacher behavior